A mini-ethnography of honey gathering: The practice and its contribution to livelihood systems in rural areas - Fajari, Muhammad Falah; Budhi, Gunawan; Umezaki, Masahiro (ETNOSIA : Jurnal Etnografi Indonesia, 2023)
As part of the people's culture, the livelihood system, various community groups in Indonesia have been practicing stinging bees honey-gathering. Many studies have reported such activities quite widely. In the context of honey-gathering activities and somewhat different from other reports, this study describes the activities of collecting honey produced by stingless bees (Tetragonula sp.) practiced by honey collectors in Sumedang Regency, West Java. The study applied the mini-ethnography method to study the honey collection and its economic system, practiced by six groups of honey collectors, by conducting participant observation and in-depth interviews. The description of study results includes knowledge systems, honey-gathering practices, social relations among the collectors, collected honey utilization, and honey-gathering practices in the context of the rural economy. This study suggests that as part of the community's livelihood system, the stingless bee honey gathering generates a significant income for honey collectors and to some extent contributes to the livelihood system in rural areas.